A cidade sem barreiras é para todos?: avaliação das condições de deslocamento no bairro da Cidade Alta, Natal/RN - Pires, Tereza Cristina Vieira (2008)
In this present work, the conditions of displacements and the behaviors of the users are evaluated, face to the physical adequacies in accessibility in the inserted area in the central quadrilateral of the Quarter of Cidade Alta, in the City of Natal/RN, space clipping established by its great meaning historical and cultural. For this reason such area was a target of an integrated actions plan during the years of 1993 and 1998, with the implantation of part of the Project CIDADE SEM BARREIRAS (City without Barriers) and, later, the implementation of the Project CIDADE PARA TODOS's proposals (City for All), having as supports the constant Brazilian norms inserted into the NB9050/1994 and in the Municipal law number 4.090/92, effective ones in the period of the interventions. Considering that the carried through actions at the time were directed to the elimination of the architectural barriers to guarantee the right to go and to come, the research received a human universe formed by all the people in situation of displacement in the central area of the interventions in the quarter of the Cidade Alta, independently of their locomotive or sensorial conditions, emphasizing the aspects most excellent how much to the accessibility of the sidewalk, as promotional of mobility, integration and urban organization, as well as of the public squares of that one quadrilateral, conceived, originally, as spaces of aggregation and social inclusion. The work appealed to the direct comment and the gotten results had been collated with the ex port facto law and technique norms, of the year of 2004, and with the legal devices contained in the Federal Decree number 5.296/2004, as way to certify the levels of efficiency of these adaptations in that it says respect to the current conditions of demanded accessibility and urban mobility